2020
DOI: 10.1080/21645515.2020.1795477
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a quadrivalent influenza vaccine in Vietnamese healthy subjects aged 6 months and older

Abstract: Quadrivalent influenza vaccines (QIVs) provide protection against the two influenza A viruses (H1N1 and H3N2) and both co-circulating influenza B lineages. QIVs have been found safe, immunogenic, and efficacious in several phase III clinical trials. Here we assess the safety of QIV after vaccination in Vietnamese infants, children, and adults. Participants (n = 228) were asked to report any solicited adverse events (AEs) occurring within 7 days, unsolicited non-serious AEs occurring within 28 days postvaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The most frequently reported solicited reactions were injection site pain, myalgia, and malaise. Overall, the QIV safety profile observed in our study appears generally similar or no worse than that reported from a clinical trial undertaken with QIV in adults in South Korea and other clinical trials conducted elsewhere, including countries in Asia across a range of age groups (though one small study did report much lower rates of myalgia and malaise [20]) [18,[20][21][22]. The frequency of AEs in our study appears generally higher than those reported in passive surveillance studies conducted in Europe [23][24][25], due likely in part to the prospective soliciting of these events using diary cards in a manner similar to clinical trials in our study.…”
Section: Discussionsupporting
confidence: 81%
“…The most frequently reported solicited reactions were injection site pain, myalgia, and malaise. Overall, the QIV safety profile observed in our study appears generally similar or no worse than that reported from a clinical trial undertaken with QIV in adults in South Korea and other clinical trials conducted elsewhere, including countries in Asia across a range of age groups (though one small study did report much lower rates of myalgia and malaise [20]) [18,[20][21][22]. The frequency of AEs in our study appears generally higher than those reported in passive surveillance studies conducted in Europe [23][24][25], due likely in part to the prospective soliciting of these events using diary cards in a manner similar to clinical trials in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Safety is an important indicator of vaccine production. Thime et al found that no serious unsolicited adverse events or vaccine-related SAEs were reported in the Phase III clinical trial [ 15 ]. When the vaccine was administered to children, the most common reaction was pain and tenderness at the injection site, but this subsided within 3 days, and there was only one unsolicited adverse reaction associated with the vaccine, but these were Grade 2 or 4 transient [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 14) An axillary temperature of ≥37.5 • C before administering the vaccine. (15) The researchers deem that some other factor compromises eligibility for this clinical trial.…”
Section: Study Populationmentioning
confidence: 99%
“…Available in 20 European markets, it will be planned to be launched in the future all around the world. It (32,33). In fact, the vaccine is a quadrivalent split-virion vaccine as a well-established record of Vaxigrip® (a trivalent split-virion flu vaccine) (34).…”
Section: Vaxigriptetra®: Quadrivalent Inactivated Influenza Vaccine (...mentioning
confidence: 99%